MEMBANGUN KEWIRAUSAHAAN PEASANT - Sedhawa, Ida Bagus (dwijenAGRO, 2010)
Poverty should be a basis on the peasant to rise themselves in overcoming their problems. They must be adaptable on the innovation, such as entrepreneurship aspect. Developing entrepreneurship one is very useful for their welfare so that they might not be marginalized anymore. This constitutes as new paradigm in agricultural development, that is, agribusiness orientation. The efforts of peasant in using agricultural inputs should be appropriate and addressed to agribusiness orientation and use low external inputs.